1995
DOI: 10.1182/blood.v86.7.2559.bloodjournal8672559
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine regulation of human megakaryocytopoiesis

Abstract: We have previously shown that platelet factor 4 (PF4), a platelet-specific CXC chemokine, can directly and specifically inhibit human megakaryocyte colony formation. We therefore hypothesized that PF4 might function as a negative autocrine regulator of megakaryocytopoiesis. Herein we present additional studies characterizing the inhibitory effect of CXC chemokines on human megakaryocyte development. We first corroborated our initial studies by showing that recombinant human (rH) PF4, like the native protein, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Another candidate to ameliorate thrombocytopenia, especially after marrow injury [5,6], is platelet factor 4 (PF4, CXCL4), a platelet-specific and megakaryocyte-specific chemokine stored in a-granules and released from activated platelets. In vitro studies have shown that PF4 is a negative regulator of human and murine megakaryopoiesis via LDL-receptor related protein-1 [6][7][8]. In mice, we have shown that steady-state platelet counts are inversely related to platelet PF4 (pPF4) content [6].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Another candidate to ameliorate thrombocytopenia, especially after marrow injury [5,6], is platelet factor 4 (PF4, CXCL4), a platelet-specific and megakaryocyte-specific chemokine stored in a-granules and released from activated platelets. In vitro studies have shown that PF4 is a negative regulator of human and murine megakaryopoiesis via LDL-receptor related protein-1 [6][7][8]. In mice, we have shown that steady-state platelet counts are inversely related to platelet PF4 (pPF4) content [6].…”
mentioning
confidence: 92%
“…Prescreening pPF4 levels in these patients may permit more intensive dosing of chemotherapy or shorter intervals between cycles, which have been associated with better event-free survival in some cancer types [10,11]. Additionally, strategies to block PF4 have been effective in altering the duration and severity of thrombocytopenia in animal models of CIT and RIT [6,7]. Therefore, prospective validation of pPF4 linkage to CIT in a variety of cancers is important as a first step in the eventual development of strategies that block PF4Õs negative paracrine effect on megakaryocytes as a therapeutic strategy for CIT.…”
mentioning
confidence: 99%
“…Chemokines are divided into two major subfamilies, CXC chemokines and CC chemokines, based on whether the first two cysteines are separated by one amino acid (CXC) or are adjacent (CC). Chemokines are known to act not only as immune and inflammatory regulators but also as regulators of haematopoiesis (Gewirtz et al . 1995;Butcher & Picker 1996;Rollins 1997;Brandt et al .…”
Section: Introductionmentioning
confidence: 99%
“…1995). However, CXC chemokines including PF-4, NAP-2 and interlukin-8, as well as CC chemokines, macrophage inflammatory protein-1 α (MIP-1 α ), MIP-1 β and C10, were found to act negatively on megakaryocyte colony formation (Gewirtz et al . 1995).…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate these studies we have also generated mutants of MIP-la which have a reduced tendency for self aggregation (Graham et al, 1994). Other members of the wider chemokine family also display proliferation regulatory functions ranging from stimulation of keratinocyte (Tuschil et al, 1992) or haemopoietic progenitor cell proliferation (Broxmeyer et al, 1990), to inhibition of endothelial cell (Gupta and Singh, 1994;Luster et al, 1995) or megakaryocyte proliferation (Gewirtz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%